Desarrollo de la inteligencia espacial a través del uso de rompecabezas en niños de 4 a 5 años de la Unidad Educativa Santo Tomás Apóstol de la ciudad de Riobamba, periodo 2021 - Moyota Mora, Alison Andrea (2022)
The main objective of this research is to develop spatial intelligence through the use of puzzles in children from 4 to 5 years old, in addition to establishing play activities for the development of spatial intelligence, the theoretical framework was based mainly on the two variables. The methodology is focused on the qualitative type of research because it is a social research, so it has a non-experimental design with a descriptive level. Information was taken from several bibliographic sources since it benefited the elaboration of this research work, the research methodology used was observation and the instruments used were an observation form directed to the children and a survey directed to the parents, both instruments contain 10 items which were used for the analysis and interpretation of the results, by means of statistical tables and graphs. As a result, the lack of a didactic resource for the development of spatial intelligence in children can be seen. As a conclusion of this research, it was concluded that it is essential to use didactic resources or materials in order to develop and maximize their abilities, participating with a didactic methodology that generates confidence, security and autonomy in children.